Frequency of dry socket among patients undergoing dental extraction presenting to Ayub Teaching Hospital - Muhammad Shakeel Saeed; Alaf Khan; Saniya Sohail; Muhammad Jamal; Anam Javed; Misbah Murtaza (Journal of University Medical & Dental College, 2022)
BACKGROUND & OBJECTIVE: Tooth extraction is the most common procedure performed at the dental office. A very well recognized and recurrent post tooth extraction complication that dental surgeons face is Dry Socket (DO) also introduced as alveolar osteitis, localized osteitis, or simply alveolitis. The objective of this study is to ascertain the frequency of dry socket among patients undergoing dental extraction at Ayub Teaching Hospital. METHODOLOGY: This descriptive cross-sectional study was performed in the department of Oral and Maxillofacial Surgery, Ayub Teaching Hospital, Abbottabad for six months. A sample size of 203 patients was predetermined using WHO a calculator. Patients of either gender from 18 to 65 years were selected. Following the standard extraction technique, detailed postoperative instructions were given. The patients were educated about the symptoms of dry socket and were requested to report immediately if he/she felt any of the said symptoms. Those patients that reported dry socket, were identified, and their data was noted on structured proforma. Statistical Package for Social sciences (SPSS) version 21 was used to analyze the data obtained. RESULTS: The Mean age recorded in present study was 35±12.00. Gender distribution showed that 155 (76.35%) patients were male and 48 (23.64%) patients were female. Mean number of days elapsed for dry socket was 5+0.57 Frequency of dry socket recorded was 12 (05.91%) patients. CONLCUSION: In this study, the results collected were found to be statistically insignificant on the accounts of trends such as female preponderance and dry socket distribution posteriorly in the mandible. Our study was in accordance with the studies in literature.